POSSIBILITIES OF USING PEDAGOGICAL TECHNOLOGIES IN TEACHING ENGLISH - Abdiraximova Z.O’.; Yuldasheva.F.F. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The article discusses the convenience and advantages of teaching English with the help of modern technology tools and the benefits of teaching with effective methods to effective students and teachers. Also, there is mentioned importance of foreign language in our technology century.